A combination of genetic algorithm and dynamic relaxation method for practical form-finding of tensegrity structures. Issue 11 (August 2022) - Bui, Hieu Quang; Kawabata, Masaya; Van Nguyen, Chinh
A combination of Genetic algorithm (GA) and Dynamic Relaxation (DR) method is presented for practical form-finding of tensegrity structures. Several approaches of dynamic relaxation method are reviewed for form-finding of tensegrity structures, and the negative points of DR method where the final form is sensitive to the initial form and cannot satisfy the geometrical constraint conditions are illustrated. The genetic algorithm is then proposed to obtain the initial configuration for DR method for finding the final shapes satisfying all constraint conditions. Several types of tensegrity structures are performed to point out the efficiency of proposed combination method.